Praxishandbuch Männergesundheit Interdisziplinärer Beratungs- und Behandlungsleitfaden - Harth, Wolfgang; Brähler, Elmar; Schuppe, Hans-Christian (MWV Medizinisch Wissenschaftliche Verlagsgesellschaft, 2012)
"New scientific findings on gender aspects reveal clear problem areas and health disadvantages for men. These include taboo subjects such as mental disorders in men, delay in doctor visits and impaired self-image in relation to health and old age. On the other hand, the role requirements as well as the individual (and also the aesthetic) health requirements of men are increasing. This book conveys multidisciplinary advice and treatment strategies for the problems with which men come into the consultation hours of doctors and therapists of all disciplines: ""New men's problems"" such as burn-out, Dorian-Gray syndrome or men's cosmetics as well as the classic topics of male medicine like such as fertility, erectile dysfunction or "menopausal symptoms". Men's health and health strategies for men can only be understood and derived using a multifactorial approach. For this purpose, numerous somatic, psychotherapeutic and social epidemiological specialists impart their specialist knowledge in this book."